The 1989 Convention on the Rights of the Child (CRC) - Benyusz, Márta (The Universal Protection of Human Rights, 2026)
Abstract: The 1989 Convention on the Rights of the Child (hereinafter referred to as CRC) is the most widely ratified human rights treaty in the world. Declaring the rights of children on a universal level filled the gap of child protection within the framework of international human rights treaties. The CRC not only established the specialised protection of children but also shifted the approach towards children from being objects of protection to subject of rights. The CRC is the catalogue of children’s rights incorporating the full range of human rights, i.e. civil, political, economic, social and cultural rights of children. The CRC was adopted by the UN General Assembly on 20 November 1989 and entered into force in September 1990.Keywords: Declaration of the Rights of the Child, United Nations, 1989 Convention on the Rights of the Child, children’s rights, Committee on the Rights of the Child